Dynamic antenna clustering along with low RF complexity digital beamforming. - Usman Haider; Syed Jawad Hussain; Imtiaz Ali Soomro; Sohaib Latif; Mrim M Alnfiai (PLoS ONE, 2025)
This paper presents a digital beamforming technique with low radio frequency (RF) complexity that can preserve antenna weights between the antenna aperture and the digital baseband processing unit. Each antenna subarray connects a separate RF chain and it can only transmit one data stream. The RF chain is made to keep the beamforming weights of subarray antenna elements in a TDM fashion. In this paper, two dynamic clustering algorithms are proposed. Using the first algorithm, the actual number of required RF chains can be identified. By using the second algorithm, it is possible to comprehend the antennas in each subarray for a specific number of RF chains. RF circuit designers can utilize the proposal from this paper to determine the exact number of RF chains in a given scenario and the corresponding digital-to-analogue converter (DAC) and its associated components. Our findings show that, with a much lower RF complexity, the suggested digital beamforming scheme can successfully deliver almost the same spectral efficiency as a full-complexity DBF system.